Instrumentación y evaluación termo-mecánica de un motor de combustión interna monocilíndrico para fines investigativos - Viloria Sierra, Bayron Elias; Melo Leal, Danilo Andres (Universidad Antonio Nariño, 2023)
This TIG is part of a research project approved by the Vice President for Science, Technology and Innovation of the Antonio Nariño University.